Estudo da variação do perfil químico de laranja pêra e tangor "Murcott" após a inoculação do fungo Alternaria alternata - Isidoro, Marsele Machado (Universidade Federal de São Carlos, 2013)
This paper describes the study of variation in the chemical profile of citrus after inoculation of the fungus Alternaria alternata, who causes the disease known as alternaria brown spot (ABS), which is one of the most serious diseases in orchards of tangerines, causing major damage to the Brazilian citrus. For this, A. alternate was inoculated in sweet orange (resistant) and Murcott tangor (susceptible) to evaluated the modification of chemical constituents through study using HPLC-DAD coupled with chemometric tools and analysis of constituents volatile of these varieties. The histopathological study of the interaction between this microorganism and citrus varieties studied was done using SEM-Environmental and was observed the penetration of the fungus into the tissue of citrus susceptible. The phytochemical study of citrus was done with the objective of obtaining substances for testing inhibition of mycelial growth and appressoria formation of A. alternata, which resulted in the isolation of 17 secondary metabolites. The chemometric analyses of the variation of the chemical profile of citrus studied detected a possible local response in leaves of Murcott Tangor. Then, to check this result was done in an experiment in 1H NMR 600 MHz and was observed a accumulation of flavonoid apigenin 7-O-rutinoside in leaves of Murcott tangor with symptoms of ABS, when compared to control of this leaves. This result stimulated the investigation of the distribution of this substance in leaves intact Murcott tangor control and leaves with symptoms of ABS, which was performed using MALDI-IMS, indicating an accumulation of this substance in symptomatic leaves of Murcott tangor.
Keywords: Produtos naturais; Perfil químico; Mancha marrom de alternaria; Microscopia eletrônica de varredura; Quimiometria; CIENCIAS EXATAS E DA TERRA::QUIMICA